The Netherlands 2024 - Woolsey, Barbara; Blasi, Abigail; Elliott, Mark; Le Nevez, Catherine; Van Geloven, Sara (Lonely Planet guidebooks., 2024)
"Lonely Planet's The Netherlands is our most comprehensive guide that extensively covers all the country has to offer, with recommendations for both popular and lesser-known experiences. Marvel at Rotterdam's architecture, sample Dutch cheese, and explore Amsterdam's Canal Ring all with your trusted travel companion"--Publisher's description.